Better Bowling: A Doing‐With Approach for Design Studio Instruction and Public Scholarship. Issue 1 (March 2014) - Wang, David; Vaux, Dana; Xu, Mengyuan
ABSTRACT This paper considers collaboration between design students and local communities to describe a doing‐with model for design studio instruction. By doing‐with, we mean direct exchanges between university design students and local communities that draw from genuine community needs to provide the basis for studio projects. This differs from traditional design studio approaches in which projects are often based on imagined programs or altered real‐world situations. In the absence of predetermined programs, this method emphasizes design as process in the delivery of design as product. Projects and solutions emerge from the real needs of the local citizenry. As the examples below will show, a doing‐with approach allows community representatives to determine the direction a project takes. This approach actively deploys students to energize a sense of community when they design projects that local residents launch. The give and take of the exchanges between university students and local residents generates design solutions that fit the local context. The doing‐with approach to actual design projects in existing neighborhoods also promotes an amenable way to generate funding.